Modification of Potato Starch by Acetylmalic Acid Chloroanhydride and Physicochemical Research of the New Product - Shulga, Oksana; Simurova, Natalia; Shulga, Sergii; Smirnova, Elizabeth (My University, 2018)
The article presents the research results of the product’s properties of potato starch modification by acetylmalic acid chloroanhydride. Modification of potato starch has been carried out and has been confirmed by elemental analysis. In the infrared spectra, changes in the frequency oscillations of native starch in the noncharacteristic region have occurred: the frequency of oscillations at 981.81 cm−1 has increased and in the spectrum of modified starch has been at 1024.82 cm−1; the band with frequency of oscillations of 923.07 cm−1 has shifted to 866.66 cm−1, and the band with frequency of oscillations of 609.79 cm−1 has shifted to 672.22 cm−1, indicating the change in noncharacteristic region of the native starch sample after acylation. The properties of obtained modified product have been studied and this modification has appeared to change the shape of moisture and starch bonds, along with decreasing appearance of grains and reduced degree of crystallinity from 12 to 4%.
Keywords: starch modification; acetylmalic acid; chloroanhydride; potato starch; крохмаль картопляний; ацетиляблучна кислота; хлорангідрид; модифікація крохмалю; кафедра експертизи харчових продуктів